Acalypha indica Linn root extract improved hippocampal cell viability and increased brain-derived neurotrophic factor (BDNF) in hypoxic condition (Faculty of Medicine Universitas Indonesia, 2012)
Background: This study was done to determine the effect of root extract of Acalypha indica Linn (akar kucing) in protecting neuron viability of the rat hippocampus on tissue culture in hypoxic condition. Methods: This is an experimental study of in vitro primary cell culture of hippocampus of Sprague Dowley adult rat. The cultures were group into control (C) and exposure to root extract of Acalypha indica Linn with dose of 10 mg/mL, 15 mg/mL, and 20 mg/mL for 72 hours. The cultures were then exposed to hypoxic gas (5% oxygen, 5% carbondioxide, nitrogen balance) for 24 hours. After that, relative cell viability was measured by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT), cell proliferation by 5-bromo2’-deoxy-uridine (BrdU), and Brain-derived Neurotrophic Factor (BDNF) levels by BDNF ELISA kit. Results: The result showed MTT viability (C: 99.7%, A indica L 10: 326.3%, A indica L 15: 411.7%, A indica L 20: 445.9%), BrdU absorbance (C: 0.07, A indica L 10: 0.10, A indica L 15: 0.12, A indica L 20: 0.13) of the exposured hippocampal cell were significantly higher than the control group (p < 0.01) accompany by increased level of BDNF (C: 11.3 pg/mL, A indica L 10: 12.5 pg/mL, A indica L 15: 23.1 pg/mL, A indica L 20: 18.1 pg/mL). Conclusion: The root extract of Acalypha indica Linn is able to improve rat hippocampal cell viability and endogenous BDNF levels in hypoxic condition. (Med J Indones. 2012;21:141-6)